Propuesta de análisis y control de riesgos ergonómicos, para el proceso productivo de piña en la Corporación de Desarrollo Agrícola del Monte División Piña, finca San Peter - Arce-Vindas, Karol Andrea (Instituto Tecnológico de Costa Rica, 2017)
The present project is carried out in the area of plant and field of the Corporación de Desarrollo Agricola Del Monte, San Peter, company dedicated to the production process of the pineapple. The aim of this study is to carry out an analysis of the ergonomic risk factors present in the pineapple production cycle, as well as to make known the main muscular-skeletal discomforts present in this process, in order to obtain a real vision of the situation to which the workers are exposed The methodology used for the analysis is based on the application of a series of methods, for the analysis of risk of corporal postures was used the method Reba and the job strain index, for the evaluation of uprisings the equation of Niosh, for the identification of ailments used the survey of músculoskeletal symptoms of Cornell University. The results show that 100% of the population presents a significant and very high risk in some part of the body, in the stowage task where the Niosh equation was applied shows that the rising rate (IL) is 5.41, therefore it results in an unacceptable risk and must be modified. With respect to the symptoms, the lower back (97%) and the wrist-hand (56%) are the area that has more ailments. In this situation, solutions are proposed to improve the working conditions through engineering controls as possible redesign of posts and equipment. Likewise, administrative controls were raised, such as: working instructions for distributing loads, and correct tasks (trainings). To implement what is proposed in this project is expected to reduce the injuries and days of disability reported by workers.
Proyecto de Graduación (Bachillerato en Ingeniería en Seguridad Laboral e Higiene Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Seguridad Laboral e Higiene Ambiental, 2017.
Keywords: Análisis de posturas; Levantamiento manual; Controles ingenueriles; Dolencias músculo-esqueléticas; Seguridad ocupacional